2021
DOI: 10.1177/17479541211055441
|View full text |Cite
|
Sign up to set email alerts
|

How do situational variables, related to shooting, in elite Gaelic football impact shot success?

Abstract: Analysis of 3926 shots from the 2019 Senior inter-county football championship aims to establish the impact of distance, angle, shot type, method and pressure on shot success. Findings demonstrate that shots from free kicks contribute 20.5% of the total attempts in Gaelic football, with a success rate of 75%, in contrast to 50% success of shots from open play. Moreover, the range from which free kick success is >57.6% accuracy extends to 40 m, while from open play this is passed at a range of 28 m. There we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…We developed a definition of a successful performance of each skill through conversations amongst our research team (see Table 1 ). In prior research, the definition of close proximity of an opponent was somewhat arbitrary; for example, both Corbett et al (2018) and McGuigan et al (2021) used “within 3m of a player on the ball.” Our definition, instead, was based on Gentile’s (1972 , 2000) concept of regulatory features; if an opponent was sufficiently close for a player to have to alter (regulate) their movement to avoid being tackled, then that opponent was deemed to be within close proximity. In Gaelic Football, if an opponent was within arm’s reach of a player’s left-hand side, they had the potential to intercept the ball if it was bounced on that side.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We developed a definition of a successful performance of each skill through conversations amongst our research team (see Table 1 ). In prior research, the definition of close proximity of an opponent was somewhat arbitrary; for example, both Corbett et al (2018) and McGuigan et al (2021) used “within 3m of a player on the ball.” Our definition, instead, was based on Gentile’s (1972 , 2000) concept of regulatory features; if an opponent was sufficiently close for a player to have to alter (regulate) their movement to avoid being tackled, then that opponent was deemed to be within close proximity. In Gaelic Football, if an opponent was within arm’s reach of a player’s left-hand side, they had the potential to intercept the ball if it was bounced on that side.…”
Section: Methodsmentioning
confidence: 99%
“…The general influence of an opponent’s proximity on task performance is well established. For example, McGuigan et al (2021) reported that, when distance and angle to the target were held constant, close proximity of an opponent reduced the probability of a score in high performance Gaelic football. Additionally, in basketball, close proximity of opposition defenders negatively impacted shot success in several basketball studies ( Alvarez et al, 2009 ; Ibáñez et al, 2008 ; Gorman & Maloney, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation